DEVELOPMENT OF STUNTED CHILDREN AGED 2-5 YEARS AT SUKOREJO HEALTH CENTRE, BLITAR CITY - Rachmawati, Dewi; Widyawati, Dwi Ajeng; Martiningsih, Wiwin (Health Gate, 2025)
Stunting is one of the nutritional problems that the government focuses on because it risks disrupting child development. This study aims to the development of stunted children aged 2-5 years at the Sukorejo Community Health Centre in Blitar City. The research method used is descriptive quantitative with a population of 91 stunted children aged 2-5 years taken by purposive sampling technique conducted on 25 March to 20 April 2024 with the DDST (Denver Development Screening Test) sheet instrument with normal interpretation if there is only 1 caution on the age line, abnormal if there are 2 or more cautions on the age line, Suspect if there are more than 2 cautions or more than 1 delay. Based on the results of the analysis of the overall development of stunted children aged 2-5 years, 75 children (82%) were normal, 7 children (8%) were abnormal, and 9 children (10%) were suspect. The conclusion in this study is that most children show normal development because parents provide regular stimulus, although there are a number of children who have delays due to lack of stimulus from parents. This study provides insight for researchers, educational institutions, health centres, and parents to increase attention to the development of stunted children.